Unsur-Unsur Pengorganisasian Sekolah - Sopan Sofian; Rolin Fadilah Hasibuan; Fachruddin Fachruddin; Makmur Syukri (Peneliti.net, 2023)
In order for a good school management to be implemented, it is necessary to have organizational elements that cannot be separated from an educational institution. The elements in an organization are in the form of vision and mission, facilities and infrastructure, cooperation between the school and the local government or other agencies. However, some schools still think that the elements in education are something that is not important, this can be seen from the many schools that have not made significant progress even though these schools have been around for a long time. The aim of the research is to be able to improve the management of school principals in empowering elements of school management. This study uses a qualitative method with the approach of observation, interviews and documentation. To obtain complete data, the researchers used the direct observation method. In developing an understanding of quality, the role of the principal as a manager is to make plans, organize all types of activities, carry out the plans to be achieved. The principal as a leader in the institution must be able to direct, build togetherness, realize the school's vision and mission to advance the school, have a strong determination to change institutions in a better direction, namely the realization of quality schools..